Analisis Hubungan Kausalitas Antara Nilai Tukar Petani dan Angka Harapan Hidup di Nusa Tenggara Timur - Putri Pamungkasih; Yuliana Kurniawati Dima; Anarela Mendonca (Jurnal Statistika Terapan (ISSN 2807-6214), 2021)
Based on data from the Statistics Indonesia (BPS) in September 2020 the poor population in rural Nusa Tenggara Timur (NTT) was 25.56 percent or around 1.05 million people. According to the 2018 Survei Tani Antar Sensus data, one of the reasons for rural farmers to be still below the poverty line is their small land ownership. With low-income sources, farmers are less able to invest in education or health issues. This study aims to see the reciprocal relationship between farmer income as measured by the farmer exchange rate (NTP) and life expectancy (AHH) in Nusa Tenggara Timur (NTT). The data used in this study are data on farmer exchange rates and life expectancy in NTT from 2008-2020. The results of the Granger causality test show that the level of farmers' income has a causal relationship with life expectancy. This means that farmers will be able to invest in health problems if their income improves. Thus, agricultural development policies are very important so that farmers can increase their income and can invest in their health problems.